Pengaruh Live Music, Store Atmosphere dan Social Media Marketing terhadap Keputusan Pembelian Generasi Z pada Merci Café Sidoarjo - Hellen Andini Arieza Rokhani; Ni Made Ida Pratiwi; Diana Juni Mulyati (Jurnal Bisnis Kreatif dan Inovatif, 2025)
At this time the coffee shop business is growing in various cities, the phenomenon of the mushrooming of cafes in Indonesia has become a common sight in various big cities to small cities, one of which is the city of Sidoarjo. Coffee shops not only function as a place to enjoy coffee drinks, but also become a social space for young people, especially generation Z. As in the city of Sidoarjo as one of the cities with quite rapid cafe growth, cafes that are always crowded with visitors because of the live music that is the hallmark of the cafe. In supporting this research, the method used is a quantitative approach method, with data collection techniques in this study being questionnaires. the results of the study showed that the live music variable had a significant effect on purchasing decisions, the store atmosphere variable had a significant effect on purchasing decisions, and also the social media marketing variable had a significant effect on purchasing decisions, in this case merci cafe must continue to pay attention to the needs of gen z by always maintaining live music facilities, and paying more attention to the cafe atmosphere to marketing on social media.